Analisis Model Pendidikan Pondok Pesantren Modern dan Sekolah Islam Terpadu - Syaidina Hamzah; Muhammad Iqbal (Journal of Islamic Education Leadership, 2023)
Model Analysis of Modern Islamic Boarding Schools and Integrated Islamic Schools. Education is a very important aspect of human life, especially in passing through the phases of human life. The implementation of education in life certainly requires a long process that contains philosophical values in educational activities. Educational activities carried out can be through formal, informal or non-formal channels. Among the institutions that carry out formal education are Modern Islamic Boarding Schools and Integrated Islamic Schools. This institution functions to develop children's potentials so that they are able to achieve the expected educational goals in accordance with the Education Law concerning the National Education System